Activities of the nurse: direct and indirect care to the hospitalized client. A descriptive study - Iraci dos Santos; Tatiane Dourado (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2007)
In the development of the nursing assistance, the role of the nurse is to create and to support practical of more humanitarian care. Then, which the activities implemented by nurse in the administration of taking care of? In this study it is had as objective to identify and to describe the activities developed for the nurse to taking care of the hospitalized client. It was chosen the analytical descriptive research through the individual interview applied to 13 residents of nursing, of general hospital of Rio de Janeiro-Brazil, in 2006. The developed activities had been categorized in direct cares, indirect cares and not developed indirect cares. It was observed the predominance of activities of forecast and provision of material and the implementation of the medicinal therapy. We conclude that, in the administration of the process of work of the nursing assistance to the client, aspects of bureaucratic character predominate. Therefore, the act of taking care in nursing implemented by the subjects of this research, although idealized as a care practice, discloses traditional aspects of a model that follows the decisions of the evaluation and medical therapy